The role of interventional radiology in pain management for multiple myeloma: a literature review - Witt, Atlee; Aujla, Saumya; Case, Meaghan Dendy (Frontiers in Hematology, 2025)
Lytic bone disease in multiple myeloma (MM) patients is cited as a major source of pain in upwards of 90% of patients, with lesions believed to exist in at least 80% of patients. Lytic bone disease increases the risk of pathologic fractures substantially, most frequently noted in the vertebrae (thoracic, followed by lumbar and cervical spine), skull, pelvis, and ribs. Even with significant advancement in the treatment of MM, such as novel chemotherapy agents and bisphosphonates, chronic pain remains a critical threat to quality of life for patients with MM. Additional factors that threaten quality of life in this population include nerve compression and infiltration, providing ample evidence of the need for effective pain relief and palliative measures as part of the MM treatment plan. The field of interventional radiology (IR) is uniquely positioned to provide targeted supportive care for patients with MM via minimally invasive, image-guided procedures that deliver effective results. This literature review investigates the role of interventionalists in providing supportive care and treatment for MM patients, focusing on procedures such as vertebroplasty and kyphoplasty, radiofrequency ablation (RFA), microwave ablation, cryoablation, high-intensity focused ultrasound (HIFU), and radiation therapy. From an interventional pain perspective, we explore nerve blocks and nerve ablations in the context of MM. Figures are derived from procedures performed at our institution to illustrate these approaches.